Effectiveness of Banana Stem, Lemongrass and Pandan Leaves Powder as Bio-coagulant and Biosorbent in Water Treatment - Ngatiman, Fakhrul Iman; Jalil, Mas Rahayu (Progress in Engineering Application and Technology, 2025)
Water quality is a critical global concern, and conventional water treatment using chemical coagulants like aluminum sulfate often has environmental drawbacks. This study evaluates the potential of agricultural by-products such as banana stem, lemongrass, and pandan leaves as sustainable alternatives for water treatment. The bio-coagulants and biosorbents were extracted using sodium chloride solution and characterized using Fourier-transform infrared spectroscopy (FTIR). Their effectiveness in reducing turbidity, stabilizing pH, and improving dissolved oxygen levels in the Muar River’s polluted water was tested using jar tests. Results demonstrated significant turbidity reduction and pH stabilization comparable to traditional coagulants. The findings suggest that natural coagulants are eco-friendly and cost-effective alternatives for enhancing water quality, promoting public health, and minimizing ecological impact